Polydiacetylene-based colorimetric and fluorometric sensors for lead ion recognition. Issue 34 (10th August 2022) - Chen, Shu-Wei; Chen, Xipeng; Li, Yang; Yang, Yalin; Dong, Yuchuan; Guo, Jinwen; Wang, Jinyi
Abstract : In this study two colorimetric and fluorometric sensors were prepared for lead ions based on conjugated polydiacetylenes. Abstract : Development of novel sensors for the detection of lead ions (Pb 2+ ) has attracted increasing interest due to their inherent toxic effects on human health and the environment. In this study, we describe two new polydiacetylene (PDA)-based liposome sensors for the colorimetric and fluorometric recognition of Pb 2+ in aqueous solution. In the sensor system, a thymine-1-acetic acid (TAA) or orotic acid (OA) group was reasonably introduced into the diacetylene monomer to work as a strong binding site for Pb 2+ . The TAA- or OA-functionalized monomer and 10, 12-pentacosadiynoic acid (PCDA) were incorporated into PDA liposomes in aqueous solution. After UV light-induced polymerization, deep blue colored liposome solutions were obtained. Upon the addition of a series of transition metal cations into the liposome solutions, only Pb 2+ could induce a color change from blue to red observable by the naked eye and a large fluorescence enhancement. The results clearly showed that the PDA–EDEA–TAA and PDA–EDEA–OA liposomes could act as highly selective and sensitive probes to detect Pb 2+ in aqueous solution. The detection limits of PDA–EDEA–TAA and PDA–EDEA–OA systems are 38 nM and 25 nM, respectively. The excellent selectivity of PDA liposomes could be attributed to the stronger complexation behavior of Pb 2+ with TAA (or OA) and the carboxylic acid at the lipid–solution interface which could perturb the PDA conjugated backbone. In addition, the proposed sensors were successfully applied to detect trace amounts of Pb 2+ in real water samples with excellent recovery, indicating that the developed method had a good accuracy and precision for the analysis of trace Pb 2+ in practical samples.